Hypertension and its association with Anthropometric indices among students in a public university - Cheah, Whye Lian; Helmy, Hazmi; Ensayan, Majorie J.; Ching, Thon Chang (Academy of Family Physicians of Malaysia, 2018)
Introduction: The present study aimed to determine the prevalence of hypertension and its association with nutritional status (body mass index, body fat percentage, and visceral fat) among students in a public university in Sarawak, Malaysia. Methods: This was a cross-sectional study among undergraduate students aged 18 years old and above. Anthropometric measurements, such as weight, height, body composition, and blood pressure measurements, were collected. Hypertension was defined as equal or more than 140/90 mmHg. Statistical analyses were done using IBM SPSS version 20. Results: A total of 354 respondents participated in the study. Mean age for the respondents was 21 years (SD 1.18 years). About 40% of the respondents were overweight or obese. Prevalence of hypertension was 8.2%. Mean systolic blood pressure was 119.1mmHg (SD14.36mmHg), and the mean diastolic blood pressure was 72.6mmHg (SD 9.73mmHg). There is a significant association between male gender (odds ratio =3.519, 95% CI is 1.886-6.566), body fat percentage (odds ratio =1.944, 95% CI is 1.050-3.601), visceral fat (odds ratio = 2.830, 95% CI is 1.346-5.951), and family history of hypertension (odds ratio= 2.366, 95% CI is 1.334-4.194) and hypertension. Conclusion: The prevalence of hypertension was less than 10% and is associated with male gender, body composition, and family history of hypertensio